Penerimaan Publik dalam Keberhasilan Mitigasi Bencana Covid-19 di Kota Samarinda - Fajar Apriani; Ahmad Luthfi; Bayu Febrianto; Junaidy Junaidy (Publisia: Jurnal Ilmu Administrasi Publik, 2022)
The Covid-19 pandemic as a non-natural disaster needs to be faced with responsiveness integrated disaster management that emphasized adaptability, collaboration and teamwork. This article analyzes public acceptance as a form of disaster response that can determine the success of the governance in implement disaster management through survey method. The research subjects are the people of the Samarinda City who became respondents randomly. Data was collected using online questionnaire that had been reliable tested. The result of the study find that the success of non-natural disaster mitigation does not always depend on cross-sectoral efforts between the government and stakeholders, but also depends heavily on the acceptability of policy targets. So it’s getting higher public acceptance of government policies, the chance of the implementation of the Covid-19 disaster mitigation success will be higher too. Because the management disasters in developing countries face great challenges from diversity characteristics of society that shape their acceptance of the policy.